Cleavage sites within the poliovirus capsid protein precursors. - Larsen, G R (1982)
Partial amino-terminal sequence analysis was performed on radiolabeled polio-virus capsid proteins VP1, VP2, and VP3. A computer-assisted comparison of the amino acid sequences obtained with that predicted by the nucleotide sequence of the poliovirus genome allows assignment of the amino terminus of each capsid protein to a unique position within the virus polyprotein. Sequence analysis of trypsin-digested VP4, which has a blocked amino terminus, demonstrates that VP4 is encoded at or very near to the amino terminus of the polyprotein. The gene order of the capsid proteins is VP4-VP2-VP3-VP1. Cleavage of VP0 to VP4 and VP2 is shown to occur between asparagine and serine, whereas the cleavages that separate VP2/VP3 and VP3/VP1 occur between glutamine and glycine residues. This finding supports the hypothesis that the cleavage of VP0, which occurs during virion morphogenesis, is distinct from the cleavages that separate functional regions of the polyprotein.